The heart in RASopathies. Issue 4 (21st November 2022) - Delogu, Angelica Bibiana; Limongelli, Giuseppe; Versacci, Paolo; Adorisio, Rachele; Kaski, Juan Pablo; Blandino, Rita; Maiolo, Stella; Monda, Emanuele; Putotto, Carolina; De Rosa, Gabriella; Chatfield, Kathryn C.; Gelb, Bruce D.; et al.
Abstract: The cardiovascular phenotype associated with RASopathies has expanded far beyond the original descriptions of pulmonary valve stenosis by Dr Jaqueline Noonan in 1968 and hypertrophic cardiomyopathy by Hirsch et al. in 1975. Because of the common underlying RAS/MAPK pathway dysregulation, RASopathy syndromes usually present with a typical spectrum of overlapping cardiovascular anomalies, although less common cardiac defects can occur. The identification of the causative genetic variants has enabled the recognition of specific correlations between genotype and cardiac phenotype. Characterization and understanding of genotype–phenotype associations is not only important for counseling a family of an infant with a new diagnosis of a RASopathy condition but is also critical for their clinical prognosis with respect to cardiac disease, neurodevelopment and other organ system involvement over the lifetime of the patient. This review will focus on the cardiac manifestations of the most common RASopathy syndromes, the relationship between cardiac defects and causal genetic variation, the contribution of cardiovascular abnormalities to morbidity and mortality and the most relevant follow‐up issues for patients affected by RAS/MAPK pathway diseases, with respect to cardiac clinical outcomes and management, in children and in the adult population.